Mantle Studies - Ludden, John; Francis, Don (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1993)
Abstract Convection in the Earth's mantle provides the driving force for plate-tectonic processes and the heat source for fluid transport in the Earth's crust. Understanding the relationships between mantle composition and convection and its interaction with continental and oceanic crust provide a major challenge to modern petrologists and geochemists. This challenge can only be re-solved by indirect studies, such as tomography and geochemical inversionson mantle-derived products, or by direct studies on rarely sampled upper mantle products in mantle xenolith suites and the barely accessible in situ outcrops on mantle in oceanic fracture zones.